Comparative effects of Cosmos caudatus, Piper sarmentosum and Premna cordifolia ethanolic extracts on mice (Mus musculus) sperm parameters - Nabihah S.; Dzulsuhaimi D.; Nooraain H. (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study was carried out to compare the effects of ethanolic extract of Cosmos caudatus (CCEE), Piper sarmentosum (PSEE) and Premna cordifolia (PCEE) on sperm parameters of male mice, Mus musculus. Twenty four sexually matured male mice were used in this study. The mice were grouped into 4 groups of 6 mice each. The first group was given 0.9% saline solution and served as a control whereas groups 2-4 were daily administered with 500 mg/kg body weight of CCEE, PSEE and PCEE respectively, orally for 30 days daily. The body weight was recorded prior to, and after the treatments. At the end of the experimental period, the mice were sacrificed by cervical dislocation. The testis and epidydimis were collected and weighed. Then, the sperm suspension was prepared and subjected to sperm analysis (sperm motility, count and morphology). Bodyweight and reproductive organ weight (testis and epididymis) were not significantly different between control and mice treated with CCEE, PSEE and PCEE. Sperm count was increased in all groups compared to control but not significantly different. Sperm motility of mice treated with PSEE significantly (p<0.05) increased compared to control. Meanwhile sperm motility was not affected by CCEE and PCEE. PCEE significantly (p<0.05) decreased the percentage of normal sperm morphology compared to control. CCEE and PSEE also reduced the percentage of normal sperm morphology but the values were not significantly different. This study proves that all of the three plants affect the sperm quality, thus further study is suggested.